1969
DOI: 10.1111/j.1570-7458.1969.tb02502.x
|View full text |Cite
|
Sign up to set email alerts
|

Vector‐induced Modifications in a Plant Virus

Abstract: The planthopper‐borne rough dwarf virus disease manifests itself on maize plants in two different groups of symptoms presumably caused by two distinct strains of the virus. The severe, dwarfing strain is transmitted to maize plants only by Laodelphax striatellus and Javesella pellucida. The milder, non‐dwarfing strain is transmissible by two additional delphacid species, namely Delphacodes propinqua and Sogatella vibix, which are unable to provoke the dwarfing‐strain syndrome on maize test plants. However, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1970
1970
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 4 publications
(4 reference statements)
0
5
0
Order By: Relevance
“…Rice dwarf virus (RDV) was found to be transmitted through 85% of the eggs of six succeeding generations of Nephotettix cincficeps (Uhler) (Chiykowski, 1981). Maize rough dwarf virus (MRDV) was reported to be transmitted to the progeny of Laodelphax striatellus (Fallen) by Harpaz & Klein (1969). RLOs associated with clover club leaf and rugose leaf curl passed through the eggs of their vectors Agalliopsis novella (Say) and Ausfroagallia torrida Evans, respectively (Chiykowski, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Rice dwarf virus (RDV) was found to be transmitted through 85% of the eggs of six succeeding generations of Nephotettix cincficeps (Uhler) (Chiykowski, 1981). Maize rough dwarf virus (MRDV) was reported to be transmitted to the progeny of Laodelphax striatellus (Fallen) by Harpaz & Klein (1969). RLOs associated with clover club leaf and rugose leaf curl passed through the eggs of their vectors Agalliopsis novella (Say) and Ausfroagallia torrida Evans, respectively (Chiykowski, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, both viruses are naturally transmitted by the small brown planthopper, Laodelphax striatellus Fallén, in a persistent manner. We suggest that more evidence is needed to support the claim that the vector can transmit MRDV through its eggs to a small proportion (4%) of the off spring (Harpaz and Klein, 1969;Milne et al, 1977a), while all other fi jiviruses are not transmitted via eggs.…”
Section: Discussionmentioning
confidence: 90%
“…(2) MRDV and RBSDV are transmitted almost exclusively by the planthopper, Laodelphax striatellus Fallén, whereas SRBSDV is transmitted by the white-backed planthopper (Sogatella furcifera Horváth) and MRCV by the planthopper Delphacodes kuscheli Fennah. (3) MRDV is transmitted through the eggs of its vector insect but RB-SDV is not (Harpaz and Klein 1969;Harpaz, 1972;Milne et al, 1977a). (4) Serological comparisons and hybridization experiments using cDNA probes also suggest that they are distinct viruses (Isogai et al, 1995;Marzachi et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…For FDV, transovarial transmission in P. saccharicida was reported but no data were included (Chang, 1977). Transovarial transmission of MRDV in L. striatellus was reported to be about 4% (Harpaz and Klein, 1969), but none of 300 progenies from L. striatellus eggs deposited on sorghum were viruliferous (Harpaz, 1972). For OSDV, only 0.2% transovarial transmission was found in one case (Vacke, 1966) and no evidence found in another case for J. pellucida (Lindsten, 1974).…”
Section: Transovarial Transmissionmentioning
confidence: 99%
“…Adverse effects include extending the nymphal stages, shortening the lifespan of adults, decreasing survival rate or fecundity (Harpaz and Klein, 1969;Nakasuji and Kiritani, 1970;Wei and Li, 2016). For example, Harpaz and Klein (1969) reported that MRDV viruliferous females of L. striatellus laid 30-50% fewer eggs than non-viruliferous females did and that the viability of these eggs was poor (14% vs. 99% for hatch from non-viruliferous). In those cases where hatching did occur, the incubation period was longer by up to 3 days (about 25%) than that of eggs from non-viruliferous females, and the mortality of the resulting larvae was high.…”
Section: Virus Effects On Behavior and Physiology Of Vector Insectsmentioning
confidence: 99%